2015
DOI: 10.1111/aos.12885
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of exfoliation syndrome in Turkey

Abstract: ABSTRACT.Purpose: To investigate the prevalence of the exfoliation syndrome and its relationship with ocular and cardiovascular diseases in the Central Anatolia region of Turkey. Methods: This cross-sectional and population-based study was conducted at the Sivas Province among the population aged 40 years and over. The diagnosis of XFS was made when exfoliative material was found on the anterior lens capsule or iris on slit-lamp examination. The subjects were divided into an XFS group and a non-XFS group accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
4
11
1
Order By: Relevance
“…This ratio was around the highest ratios reported so far. PSXG patients comprised the oldest patients in the overall group and, similar to a previous study from Turkey, there was male preponderance [24]. Bilateral involvement in these patients was present in 77% of our series, similar to the previous reports [16,23].…”
Section: Ankara Is the Capital And The Second Largest City Of Turkey supporting
confidence: 92%
See 1 more Smart Citation
“…This ratio was around the highest ratios reported so far. PSXG patients comprised the oldest patients in the overall group and, similar to a previous study from Turkey, there was male preponderance [24]. Bilateral involvement in these patients was present in 77% of our series, similar to the previous reports [16,23].…”
Section: Ankara Is the Capital And The Second Largest City Of Turkey supporting
confidence: 92%
“…In Greece, another neighbor to the west of Turkey however, clinic-based study revealed that PSXG is probably responsible for the majority of severe cases of glaucoma [23]. In a recent population-based study, PSX syndrome has been shown to be common in Turkey [24]. In a study from Eastern Mediterranean area of Turkey, percentage of PSX syndrome in patients with open-angle glaucoma was 46.9% [25].…”
Section: Ankara Is the Capital And The Second Largest City Of Turkey mentioning
confidence: 99%
“…Other researchers also found similar trends in the interactions between AH and the PEX [7,31]. This may be due to the fact that persons with AH have effectively controlled their blood pressure, thereby reducing the risk of developing the PEX.…”
Section: Discussionmentioning
confidence: 56%
“…The opposite results were found in Turkey, where higher rates of cerebrovascular disease in the PEX group were observed [28]. Many studies did not find any significant differences between the rates of AH and the PEX [7,15,[29][30][31]. In the followup study, we could not confirm the baseline data of the significant association of the rates of AH and higher systolic blood pressure with the PEX because of the small size of the sample and a higher number of risk factors in older age [9].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation